Repeated games with partner choice - Christopher Graser; Takako Fujiwara; Julián García; Matthijs van Veelen (Tinbergen Institute, 2024)
Repetition is a classic mechanism for the evolution of cooperation. The standard way to study repeated games is to assume that there is an exogenous probability with which every interaction is repeated. If it is sufficiently likely that interactions are repeated, then reciprocity and cooperation can evolve together in repeated prisoner's dilemmas. Who individuals interact with can however also be under their control, or at least to some degree. If we change the standard model so that it allows for individuals to terminate the interaction with their current partner, and find someone else to play their prisoner's dilemmas with, then this limits the effectiveness of disciplining each other within the partnership, as one can always leave to escape punishment. The option to leave can however also be used to get away from someone who is not cooperating, which also has a disciplining effect. We find that the net effect of introducing the option to leave on cooperation is positive; with the option to leave, the average amount of cooperation that evolves in simulations is substantially higher than without. One of the reasons for this increase in cooperation is that partner choice creates endogenous phenotypic assortment. The model thereby produces a good match with many forms of human cooperation in repeated settings, where we end up interacting, not only with random others that we cannot separate from, once matched, or with others that are genetically related to us, but also with partners that we choose to stay with, and that end up being similarly dependable not to defect on us as we are not to defect on them.
Keywords: C73; 330; Wiederholte Spiele; Theorie